African culture and managerial behaviour: Clarifying the connections - P. Mufune (South African Journal of Business Management, 2003)
There is an increasing recognition that Management is a critical factor in the running of African organizations and in pulling African countries out of their economic crisis. Although efforts have been made to provide management and administrative training, the role of culture in management remains poorly understood. This paper evaluates studies that look at the role played by African culture in managerial behaviour. It examines how values and approaches derived from African culture may or may not be affecting managers and the functioning of organizations. It examines how African managers diverge from managers in other countries. It concludes by emphasizing that there are many shortcomings in research on the African culture-managerial behavior dynamic. It points to various suggestions that may help clarify the inconclusive results in this area of research.
Keywords: 650